Phenolic and Antioxidant Activity of Moringa-Bean Sprouts Extract as PGRs for Soybeans - Itsnaini, Putri Nur; Anggarani, Mirwa Adiprahara (Jurnal Pijar Mipa, 2025)
The demand for soybeans continues to increase, but local production remains insufficient, requiring strategies to enhance productivity and quality, such as the application of Plant Growth Regulators (PGRs). Natural PGRs derived from moringa leaves and mung bean sprouts, which are rich in auxins and cytokinins, have the potential to accelerate growth and stimulate the production of secondary metabolites. This study investigated various proportions of moringa leaf and mung bean sprout extracts to evaluate their phenolic content, antioxidant activity, and potential as natural PGRs in soybean cultivation. The extracts were analyzed using the Folin–Ciocalteu method for total phenolics and the DPPH assay for antioxidant activity. Among the treatments, Variation E, with a higher proportion of mung bean sprout extract, proved to be the most effective, enhancing both antioxidant activity and phenolic compound production. These findings highlight the novelty of combining moringa leaf and mung bean sprout extracts as a natural PGR strategy, demonstrating promising potential to support soybean growth and improve crop quality.